2007
DOI: 10.1016/j.jastp.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale thermodynamics of the stratosphere and mesosphere during the major stratospheric warming in 2003/2004

Abstract: The stratosphere-mesosphere response to the major sudden stratospheric warming (SSW) in the winter of 2003/2004 has been studied. The UKMO (UK Meteorological Office) data set was used to examine the features of the large-scale thermodynamic anomalies present in the stratosphere of the Northern Hemisphere. The vertical and latitudinal structure of the genuine anomalies, emphasized by removing the UKMO climatology, has been investigated as well. The features of the stratospheric anomalies have been related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…They found no evidence for a continuous westward wind band between the pole and 20 • N in the average behaviour of a warming in the lower stratosphere up to 32 km. This polar activity of SSW effects without a continuous westward wind band from the pole to lower latitudes is also observed in case studies for individual events, as for example in Hoffmann et al (2007) and especially in Mukhtarov et al (2007). Therefore, the events studied here are exceptional even if they occur in a temporally short interval.…”
Section: Discussionsupporting
confidence: 75%
“…They found no evidence for a continuous westward wind band between the pole and 20 • N in the average behaviour of a warming in the lower stratosphere up to 32 km. This polar activity of SSW effects without a continuous westward wind band from the pole to lower latitudes is also observed in case studies for individual events, as for example in Hoffmann et al (2007) and especially in Mukhtarov et al (2007). Therefore, the events studied here are exceptional even if they occur in a temporally short interval.…”
Section: Discussionsupporting
confidence: 75%
“…in zonal mean temperature. Mukhtarov et al (2007) using the UK Met. Office (UKMO) data investigated the latitudinal structure of the genuine stratospheric anomalies (emphasized by removing the UKMO climatology) related to the major SSW in the Arctic winter of 2003/2004 and found that: (i) warmings at high latitudes are associated with coolings at low-middle and tropical latitudes, and (ii) negative zonal mean zonal wind anomalies (deceleration/reversal of the eastward winter flow) at high latitudes are linked with the positive (amplification of the eastward flow) anomalies at low-middle and tropical latitudes; these effects are particularly strong in the upper stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003/2004 winter when we concentrate our case on, a major SSW event is found in north hemisphere that led to polar vortex disruption [37]. Pancheva and Mukhtarov et al [20][21][22] extracted 11-and 17-day waves in the stratosphere at the same time. Our study also confirms the remarkable existences of quasi 10-day and quasi-16-day waves there.…”
mentioning
confidence: 96%
“…Meanwhile, a few researchers have paid attention to stratosphere [20][21][22]. However, troposphere, where PWs originate, is rarely studied and reported.…”
mentioning
confidence: 99%